2014
DOI: 10.1016/j.amepre.2013.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for Cancer Prevention During Midlife

Abstract: This paper provides highlights from a CDC-hosted meeting on opportunities for cancer prevention during midlife (roughly ages 45–64 years). Positive changes during this phase of life have the potential to prevent cancer incidence later in life, making this phase an opportune time for targeted prevention efforts to facilitate healthy aging and increased longevity. Risk and protective factors discussed during the meeting included exposure to radiation from medical imaging procedures, circadian disruption, chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 56 publications
(65 reference statements)
1
12
0
Order By: Relevance
“…111 The workshop summary in this supplement highlights potentially promising approaches and strategies for cancer prevention at midlife. 112 …”
Section: Resultsmentioning
confidence: 99%
“…111 The workshop summary in this supplement highlights potentially promising approaches and strategies for cancer prevention at midlife. 112 …”
Section: Resultsmentioning
confidence: 99%
“…studies of breast cancer have found that early life exposures during puberty are important determinants of adult breast cancer risk. [23] Other potential mechanisms important for cancer risk include a chronic lack of access to healthcare that minimizes the opportunity for appropriate medical recommendation about cancer risk[24], the higher burden of psychosocial stressors, as well as exposures to environmental pollutants, including lead and infectious agents such as H. Pyori.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Fortunately, evidence-based cancer prevention strategies for ameliorating such risk factors are growing. 3,4 Although less is known about what specific interventions should be targeted to particular age groups to reduce cancer risks, there is growing recognition of the value of combining a life-course perspective with public health frameworks and interventions that can be applied to cancer prevention and control.…”
Section: Introductionmentioning
confidence: 99%